Den topografiske vending og læring i praksis - Szulevicz, Thomas; Nielsen, Klaus (Slagmark - Tidsskrift for idéhistorie, 2018)
The educational research and practice field usually does not incorporate concepts such as space, place and materiality in the understanding of learning in any concerted way. Traditionally learning has instead either been understood as a cognitive phenomenon or a socially constructed process. In particular, the cognitive understanding of learning has gained influence in our education system. Drawing on British anthropologist, Tim Ingold’s Heidegger-inspired understanding of learning as dwelling, this article presents an alternative to the cognitive understanding of learning. The article reports from an ongoing research project at an agricultural school for young students with learning difficulties. Videorecorded observations of a student with learning difficulties learning to milk in a milking pit are presented and used to discuss learning from a dwelling perspective. It is argued that students’ participation and active engagement in authentic learning settings both facilitate their learning and professional identity development.